Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Manajemen Usaha Rumahan di Kecamatan Medan Tembung - Harahap, Cece (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Housewives in urban areas such as Medan Tembung District have great potential as economic actors, but are often constrained by low managerial skills and limited market access. This community service program aims to empower housewives through home-based business management training covering business planning, simple financial recording, and digital marketing strategies. The implementation method was carried out systematically through four stages: needs identification, training design preparation, practice-based training (learning by doing), and intensive mentoring for two weeks. The results showed a significant increase in participants' understanding, measured through pre-test and post-test with an average increase of 35%. Participants are now able to separate personal finances from business capital and have begun utilizing digital platforms such as WhatsApp Business to expand their marketing reach. Furthermore, the formation of a local business community is an important output to ensure program sustainability. In conclusion, strengthening managerial capacity accompanied by continuous mentoring effectively increases financial independence and the competitiveness of home-based micro-businesses.